2014
DOI: 10.1016/j.ecoser.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation games that integrate research, entertainment, and learning around ecosystem services

Abstract: a b s t r a c tHumans currently spend over 3 billion person-hours per week playing computer games. Most of these games are purely for entertainment, but use of computer games for education has also expanded dramatically. At the same time, experimental games have become a staple of social science research but have depended on relatively small sample sizes and simple, abstract situations, limiting their range and applicability. If only a fraction of the time spent playing computer games could be harnessed for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Considering that ecosystem services value (ESV) represents a collective sum of utilitarian and non-utilitarian values from the artificial wetland ecosystem [19], we use it as the primary indicator for measuring the benefits of the artificial wetland. The spillover effect resulted from the ecological restoration of the artificial wetland is also included as a type of benefit in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that ecosystem services value (ESV) represents a collective sum of utilitarian and non-utilitarian values from the artificial wetland ecosystem [19], we use it as the primary indicator for measuring the benefits of the artificial wetland. The spillover effect resulted from the ecological restoration of the artificial wetland is also included as a type of benefit in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Urban ecosystems are increasingly threatened by urban population growth, urban land use expansion(Storkey, Döring et al 2015, Leverkus and Castro 2017, Yang, Guan et al 2018, Kuriqi, Pinheiro et al 2019), and socio-economic activities(Mensah, Veldtman et al 2017, Song and Deng 2017), which affects the value of ecosystem services and ultimately the sustainable development of human society(Costanza, d’Arge et al 1997, Sun, Liu et al 2016). Accurate assessment of ecosystem services value (ESV) is essential for urban construction planning and the improvement and restoration of urban ecosystems(Cui, Xiao et al 2017), so it has received increasing attention from the research community(Costanza, Chichakly et al 2014, Costanza, De Groot et al 2014, Leverkus and Castro 2017, Ossola and Hopton 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Monetary valuation of the importance of ecosystem services to society can serve as a powerful and essential communication tool to provide a basis for better and more balanced decisions(De Groot, Brander et al 2012). Scholars have found that basic income transfers can be a convenient way to determine ESVs globally and nationally, assuming a constant unit value per hectare for a given ecosystem type multiplied by the area of each type to arrive at a total (Costanza, De Groot et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This approach can make a revolution in ecosystem service research and assessment. Simulation games could contribute to understanding and managing ecosystems in the public interest [30].…”
Section: Introductionmentioning
confidence: 99%